Neural network approach for estimating state of charge of lithium-ion battery using backtracking search algorithm - Hannan M.A.; Lipu M.S.H.; Hussain A.; Saad M.H.; Ayob A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Backpropagation; Backpropagation algorithms; Charging (batteries); Electric batteries; Electric vehicles; Errors; Ions; Learning algorithms; Learning systems; Lithium; Lithium-ion batteries; Mean square error; Neural networks; Optimization; Radial basis function networks; Secondary batteries; Torsional stress; Back propagation neural networks; Backtracking search algorithms; Battery residual capacity; Extreme learning machine; Generalized Regression Neural Network(GRNN); Mean absolute percentage error; Radial basis function neural networks; State of charge; Battery management systems